2021
DOI: 10.1021/acs.jpcb.1c05815
|View full text |Cite
|
Sign up to set email alerts
|

Stationary and Time-Dependent Carbon Monoxide Stretching Mode Features in Carboxy Myoglobin: A Theoretical–Computational Reappraisal

Abstract: The stationary and time-dependent infrared spectrum (IR) of the CO stretching mode (νCO) in carboxymyoglobin (MbCO), a longstanding problem of biophysical chemistry, has been modeled through a theoretical–computational method specifically designed for simulating quantum observables in complex atomic–molecular systems and based on a combined application of long time scale molecular dynamics simulations and quantum-chemical calculations. This study is basically focused on two aspects: (i) the origin of the stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…For bonded ligands in the wild type sperm whale MbCO, four different substates related to CO stretching vibrations denoted as A 0 , A 1 , A 2 and A 3 (with the frequencies of a value of 1965, 1947, 1942, and 1932 cm −1 , respectively) were observed 209–212 . The protein substates were assigned to His64–open and closed conformational states as well as local effects of the amino acids, different sizes of the cavities, or certain interactions between His64 and FeCO 213–217 . It has been suggested that the differences observed among the various CO stretching conformers stem from changes in the electrostatic interaction between the heme pocket and the CO that is coordinated to the Fe atom of the heme group 218 .…”
Section: Comparison With Mbcomentioning
confidence: 99%
See 3 more Smart Citations
“…For bonded ligands in the wild type sperm whale MbCO, four different substates related to CO stretching vibrations denoted as A 0 , A 1 , A 2 and A 3 (with the frequencies of a value of 1965, 1947, 1942, and 1932 cm −1 , respectively) were observed 209–212 . The protein substates were assigned to His64–open and closed conformational states as well as local effects of the amino acids, different sizes of the cavities, or certain interactions between His64 and FeCO 213–217 . It has been suggested that the differences observed among the various CO stretching conformers stem from changes in the electrostatic interaction between the heme pocket and the CO that is coordinated to the Fe atom of the heme group 218 .…”
Section: Comparison With Mbcomentioning
confidence: 99%
“…For MbCO it is widely recognized that substates A 0 and A 1 correspond to the His64–open and closed conformational states while the origin of substate A 3 has been a highly debated subject; some investigations having proposed the following to explain its origin: (1) the local field– effect enabled by amino acids, (2) differing size of the cavities, (3) certain interactions between His64 and FeCO 213–216 . However, more recent work has revealed that the origin of A 3 , as well as A 0 and A 1 , is solely attributed to the H–bond interaction between FeCO and His64 that, in turn, result in the His64–open and closed conformations; the free energy difference between the two conformations was found to be between 4 and 5 kJ/mol 217 . It also has been speculated that different protein conformations of varying substates, various mutations, and the presence of solvent near prosthetic groups may govern the time it takes for the excited state of the CO stretching mode in MbCO to reach the lowest excited vibrational state 223,224 …”
Section: Comparison With Mbcomentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to emphasize two key aspects of the method: (i) as compared to the typical quantum mechanic/molecular mechanic (QM/MM) methods [46], the QC and the rest of the system are simulated using the same Hamiltonian (typically. empirical force fields); (ii) the above definition of the QC, i.e., the simplest, in some cases, might be not suitable [47], and in these cases, its definition should be addressed critically and according to the problem at hand. More explicitly, the computational strategy of PMM is based on the a posteriori evaluation at each frame of the MD trajectory of the electronic and magnetic properties of the QC, along with the rest of the system, i.e., the solvent, acting as an electrostatic perturbation.…”
Section: Resultsmentioning
confidence: 99%